THE URGENCY OF EDUCATION AND LITERACY OF WAQF IN MUSTHAFAWIYAH ISLAMIC BOARDING SCHOOLS - Mayurida Mayurida; Anwar Anwar; Mhd Hasbi (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine the urgency of education and literacy of waqf in the Musthofawiyah Islamic boarding school. Islamic boarding schools are one of the official institutions of Islamic education in Indonesia, as a place to study religious knowledge in understanding Islamic law in kaffah. Waqf as Islamic law is also studied at the pesantren but the problems encountered are education and literacy of waqf is very minimal, even almost It is not understood by the Santri except only understanding the general definition and the law alone, there is no contemporary waqf literacy as material in exploring the history, benefits and developments of success in managing waqf in accordance with the mandate of the law. The method used in this research is qualitative with a case study approach. And as for the results of this study is that education and literacy of waqf in the Mustofawiyah Islamic boarding school is very minimal, because the material of waqf is only obtained during additional recitation outside the classroom. Teachers do not understand the development of contemporary waqf, Santri do not get waqf literacy in the library as reading material in understanding contemporary waqf. The impact of the lack of knowledge of waqf is that there is no awareness of waqf and the willingness to do waqf, so that in Musthofawiyah there is no waqf movement. In this case, with the birth of the Indonesian Waqf Movement (GERAKIN), it is hoped that there will be cooperation with boarding school in the development of waqf education and literacy and become one of the curricula in the pesantren so that what the government hopes for the community to understand waqf departs from these students as social beings who will be in direct contact with the community through their preaching, in this case education and literacy of waqf is very important in Islamic boarding school to support the program of the Indonesian waqf body and the implementation of the boarding school as an official institution to carry out the mandate of the law on waqf.Keywords: Education Urgency, Waqf literacy in Islamic boarding schools